2018
DOI: 10.1007/s11356-018-3071-2
|View full text |Cite
|
Sign up to set email alerts
|

Roles of hydrophobic and hydrophilic fractions of dissolved organic matter in sorption of ketoprofen to biochars

Abstract: Hydrophobic acid (HoA) and hydrophilic neutral (HiN) are two major fractions of dissolved organic matter (DOM). Their role in the sorption of ketoprofen (KTP) to wheat straw-derived biochars pyrolyzed at 300 °C (WS300) and 700 °C (WS700) was investigated to further probe the mechanisms responsible. WS700 has much higher pore volume and specific surface area (SSA) than WS300. Loading of HoA and HiN resulted in surface coverage of biochars. HoA with larger molecular size led to more pore blockage of biochars tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Several observations for effect of DOM on sorption of organic pollutants by biochar have been reported, including competition for adsorption sites, pore blockage by DOM coating and provision of extra sorption sites or partitioning phase for organic pollutants (Lian et al 2015;Wu et al 2018a;Zhang et al 2015). The increased K p after addition of DHA was directly attributed to enhanced partitioning of BTA into DHA covered on biochar, which was supported by the observed results of BTA sorption to DHA (Fig.…”
Section: Effect Of Dha On Bta Sorptionsupporting
confidence: 67%
See 1 more Smart Citation
“…Several observations for effect of DOM on sorption of organic pollutants by biochar have been reported, including competition for adsorption sites, pore blockage by DOM coating and provision of extra sorption sites or partitioning phase for organic pollutants (Lian et al 2015;Wu et al 2018a;Zhang et al 2015). The increased K p after addition of DHA was directly attributed to enhanced partitioning of BTA into DHA covered on biochar, which was supported by the observed results of BTA sorption to DHA (Fig.…”
Section: Effect Of Dha On Bta Sorptionsupporting
confidence: 67%
“…New evidence presents the fact that the sorptive activities of biochar for organic contaminants can be strongly influenced by coexisting dissolved organic matter (DOM) in the environment (Zhang et al 2015). It was found that DOM reduced sorption of organic contaminants to carbonaceous materials via competition or hindering the accessibility of adsorption sites (Engel and Chefetz 2016;Wu et al 2018a). In addition, the competition may vary under different conditions since sorption of DOM to solid phase can be affected by different types of cations (Kalbitz et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the overall effect depends largely on the individual combination of the ternary mixture of soil—PhACs—slurry and especially on the composition of the slurry. This has been investigated in studies focusing on the soil sorption of PhACs in the presence of slurry from different sources and slurry fractions such as dissolved organic matter (DOM) and polarity fractions (e.g., [ 37 , 38 , 39 , 40 ]). In contrast, the impact of different chemical components of manure has, to the best of our knowledge, not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%